Polsko-, niemiecko- i rosyjskojęzyczny obraz „innego” i „obcego”. Analiza porównawcza pól asocjacyjnych - Gawarkiewicz, Roman (Studia Rossica Posnaniensia, 2020)
The article is concerned with reconstructing the cultural meanings included in the Polish signs “inny” (“different”) and “obcy” (“foreign”) and comparing them with their Russian and German counterparts, i.e. “другой” and “чужой”, “der Andere” and “der Fremde” respectively. The data for the comparative analysis were collected by means of the free association method. The features indicated by the respondents reflected culture-specific and language-specific associative profiles of images of the lexical items “different” and “foreign”, characteristic of the representatives of the Polish, Russian and German cultures. The results of the association test confirm that there exist numerous criteria which the Polish, Russian and German respondents referred to while specifying the meaning of “different” and “foreign”. The questionnaire allowed for establishing a hierarchy of the criteria as well as for indicating significant similarities and differences between the Polish, Russian and German associative definitions of both terms.